Regime-based transition intermediaries at the grassroots for community energy initiatives. (April 2021) - Boyle, Evan; Watson, Clare; Mullally, Gerard; Ó Gallachóir, Brian
Abstract: This paper investigates the support network surrounding community energy initiatives in Ireland and the potential for locally embedded organisations- which are co-ordinated centrally but consist of nation-wide local factions built on volunteerism- to act as regime-based transition intermediaries at the grassroots level to support the development and scaling up of projects in the community energy space. Building on the transition literature on intermediation, we take an innovative approach to network mapping to highlight the organisations, agencies and intermediaries supporting 9 of the most developed community energy initiatives in Ireland. On from this, we investigate the potential of a regime-based transition intermediary to support community energy at the local level, taking the Tidy Towns as the organisation under investigation. Within this, locally embedded organisations are suggested as having the ability to play a networking function for the scaling up of community energy initiatives through network development and trust building, aligning with the need to expedite the transition to a low-carbon society.